2007
DOI: 10.1080/13676260701597243
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Students’ Attitudes towards Commercialised Sex

Abstract: The article examines attitudes towards sexuality and its commercial representations among Finnish students aged 18Á30. In order to evaluate commercialised sex as broadly as possible, we approached it from three angles: sex as a special effect in media and marketing; display of a 'sexy' body and clothing as a part of young person's identity; and sex or pornography as a direct purchase that involves transaction of money or other goods. Empirical measures addressing these three angles are constructed for the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…The prostitution myth may be attributed to marketing by media (Coy et al 2011). Primarily, the wide availability of pornography may lead to justification of commercialized sex and prostitution by depicting prostitutes as not victims of sexual exploitation, but as sluts (Räsänen and Wilska 2007;Strøm 2009). Thus, it is pertinent to stop glamourizing sex and prostitution by media (Coy et al 2011).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The prostitution myth may be attributed to marketing by media (Coy et al 2011). Primarily, the wide availability of pornography may lead to justification of commercialized sex and prostitution by depicting prostitutes as not victims of sexual exploitation, but as sluts (Räsänen and Wilska 2007;Strøm 2009). Thus, it is pertinent to stop glamourizing sex and prostitution by media (Coy et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, Stack et al (2010) reported that younger individuals and males are more tolerant toward prostitution than older aged ones and females. Basow and Campanile (1990) also found that women are more likely to exhibit an unfavorable attitude toward prostitution (see also Cosby et al 1996;May 1999;Räsänen and Wilska 2007). Prostitution may facilitate infidelity among married couples in which the husband patronizes prostitutes, which may account for women's more negative attitude Cao and Maguire 2013).…”
Section: Other Factors Influencing Attitudes Toward Prostitutionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two other studies used data from other nations (Peracca, Knodel, & Saengtienchai, 1998;Rasanen & Wilska, 2007). Peracca et al (1998) utilized 88 adults in Thailand in a focus group design to simply demonstrate that while there was a strong negative view of sex workers, a majority of focus group participants thought that it was acceptable for sex workers to marry.…”
Section: Research On the Attitude Toward Prostitutionmentioning
confidence: 97%
“…Introducción L a preocupación por la apariencia física se ha incrementado en las últimas décadas considerándose parte esencial dentro del proceso de construcción de la identidad del individuo y su posterior realización (Sarpila, 2012, Featherstone, 2007Turner, 2008;Shilling, 2003;Gill, Henwood y McLean, 2005). Esta situación ha contribuido a impulsar el consumo de productos de belleza y cuidado personal dentro del segmento femenino (Sarpila y Räsänen, 2011), el cual es un público tradicionalmente asociado con dicha categoría (Berg y Teigen, 2008;Räsänen y Wilska, 2007). Al respecto, de acuerdo con Euromonitor (2017), entre 2011 y 2016, la categoría belleza y cuidado personal ha crecido en promedio 4.87 % anual en el mundo, situándose América Latina por encima del promedio con un crecimiento de 8.82 % durante ese mismo periodo.…”
unclassified